Terjemahan subulus salam: hadits-hadits hukum - Ash_Shon'ani (Al Ikhlas, 1991)
tr, jil. 1=c.1-2; jil. 2=c.1-6; jil. 3=c.1-3/oen, jil.2=c.7; sn,jl.1,c.3-5, jl.3,c.2/tr, jil. 2=c.8/ir, jil.1,c.6 ; jil.2,c.9-10